Fear of Recurrence and Progression in People with Heart Disease: Risk Factors and Implications for Emotional Support - Sarah T. Clarke; Barbara M. Murphy; Robert Hester; Alun C. Jackson (Behavioral Sciences)
Support to manage fear of recurrence and progression (FoRP) is a major concern and a commonly unmet need for people with chronic illness. The current study identified profiles of and risk factors for FoRP in people with heart disease. A sample of 241 participants completed 44 cardiac-specific FoRP items and provided demographic, clinical, and psychosocial information. Cluster analysis identified three profiles: a high-, moderate-, and low-FoRP group. Patients who were younger, had a comorbid health condition(s), and higher levels of uncertainty and cardiac-related distress were at the most risk of higher FoRP. By characterizing the nature and correlates of cardiac-FoRP, this study enables health professionals to understand the specific concerns of their patients and assists in identifying those at greatest risk. The findings extend the emerging field of cardiac-FoRP research and will assist in the development of a cardiac-specific screening measure and of tailored and targeted interventions to support cardiac patients in their emotional recovery.